2018
DOI: 10.1007/s00059-018-4723-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of angiographically visible distal embolization in STEMI

Abstract: AVDE complicating p‑PCI with thrombectomy in STEMI is frequent (17%) and a successful thrombectomy does not rule out AVDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Parameters for improved reperfusion, such as myocardial blush grade and ST‐segment resolution are consistently improved with manual aspiration, however a correlation with decreased mortality or MACE has not been demonstrated 25,26 . Although these were not recorded in our registry, these parameters could have contributed to improved post‐procedural TIMI 3 flow and overall procedural success, despite increased rates of transient and persistent no‐reflow.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Parameters for improved reperfusion, such as myocardial blush grade and ST‐segment resolution are consistently improved with manual aspiration, however a correlation with decreased mortality or MACE has not been demonstrated 25,26 . Although these were not recorded in our registry, these parameters could have contributed to improved post‐procedural TIMI 3 flow and overall procedural success, despite increased rates of transient and persistent no‐reflow.…”
Section: Discussionmentioning
confidence: 83%
“…Parameters for improved reperfusion, such as myocardial blush grade and ST-segment resolution are consistently improved with manual aspiration, however a correlation with decreased mortality or MACE has not been demonstrated. 25,26 Although these were not recorded in our registry, these parameters could have contributed to improved post-procedural TIMI 3 flow and overall procedural success, despite increased rates of transient and persistent no-reflow. Additionally, postprocedural Q-waves were also not recorded, and although decreased rates in previous TA groups were considered secondary to myocardial salvage, this has not been linked to improved short or long-term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a lower degree of distal embolization in smaller infarct‐related arteries. 5 , 8 , 9 Despite this observation, smaller culprit lesion vessel size has been identified as an independent predictor of adverse outcomes in patients treated with primary PCI for STEMI. 5 , 6 This represents a complex and somewhat paradoxical relationship, considering the role of distal embolization in microvascular injury and its substantial prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 On the other hand, few studies have examined the relationship between culprit lesion vessel size and myocardial reperfusion with conflicting results. 5 , 8 , 9 Moreover, an important limitation of these studies was the lack of comprehensive myocardial tissue characterization by CMR imaging to accurately determine reperfusion success. Therefore, the pathophysiology of myocardial reperfusion injury in relation to culprit lesion vessel size in acute STEMI is incompletely understood.…”
mentioning
confidence: 99%
“…Percutaneous coronary interventions (PCI) in acute settings differ significantly from planned procedures. During primary PCI, any instrumentation in the vessel with a high thrombus burden increases the risk of distal embolization (DE), worsening the patient’s prognosis [ 1 ]. Thrombectomy was introduced to mitigate myocardial damage caused by DE but did not appear to be better in comparison to PCI alone in the TOTAL study [ 2 ].…”
mentioning
confidence: 99%